Registers of psoriatic arthritis. Literature review - A. D. Koltakova (Научно-практическая ревматология)
Observational cohort investigations are an effective way to study chronic diseases, including psoriatic arthritis, in clinical practice. One of the tools to support such research is registers that collect data related to various aspects of the disease and pharmacotherapy. This review provides information on the main registers of patients with psoriatic arthritis.